FISH BEHAVIOR ON FISHERIES BOAT LIFT NET (BAGAN PETEPETE) BY USING LED LIGHTS - Muhammad Sulaiman; Mulyono Sumitro Baskoro; Am Azbas Taurusman; Sugeng Hari Wisudo; Roza Yusfiandayani (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
Research on fish behavior in boat lift net fisheries (bagan petepete) equipped with LED light is very important since the similar research is very limited conducted in Indonesian waters. The purpose of this study was to understand the LED light distribution and its impact on the fish behavior around the LED light. This study was conducted in the laboratory of Simulation Workshop and Navigation, Pangkep State Polytechnique of Agricultural and fishing experiment was done in Barru District waters, Makassar Strait, South Sulawesi. The light intensity was measured by a digital lux meter and under water lux meter, while fish behavior was observed by side scan sonar color. Light intensity analyses showed that the distribution of 80 watts LED light was mostly focused with 1096 lux with an angle168°. Fishes approached the light at 5-10 m and 20-30 m water depth from all directions after all lights were turned on. Fishes in smaller groups and higher density concentrated around the light when only one lamp was turned on. After catch processing, some fishes left the lighting area and others still stayed in the lighting area. Keywords: fish behavior, LED lamp, light fishing, lift net